Evaluation of Eco-environmental Vulnerability of Pearl River Delta Based on PSR Model - Zheng Huiling; Wang Yonghong; Ma Wei (Shuitu baochi tongbao)
[Objective] The spatio-temporal evolution characteristics and its reasons of eco-environmental vulnerability in the Pearl River delta were studied in order to provide theoretical basis for regional development. [Methods] The pressure-sensitivity-restoration (PSR) model, quantitative grading method and analytic hierarchy process (AHP), as well as the combination of the eco-environmental vulnerability index were used to analyze the characteristics of eco-environmental vulnerability of the Pearl River delta at different periods. On this basis, the degree of influence of variable factors on differences in the spatio-temporal distribution of ecological vulnerability was analyzed with the help of factor detection of Geodetector. [Results] ① From 2000 to 2020, the eco-environmental vulnerability index ranged from 1.206 5～4.594 8, indicating slight vulnerability grade. ② In terms of spatial distribution, the vulnerability level was higher in the central part of the Pearl River delta and lower in the eastern and western. In addition, with the increase of elevation, the degree of eco-environment vulnerability tended to decrease on the whole, the proportion of moderate and severe vulnerability decreases. ③ Forest land exhibits potential and slight vulnerability grade, grassland showed moderate vulnerability, cultivated land, water and unused land are mainly located in mild vulnerability areas and construction land showed severe and moderate vulnerability grade. ④ The main factors influencing the spatial variation of eco-environmental vulnerability in the Pearl River delta were population density, NDVI and biological richness index. [Conclusion] Affected by the pressure of population growth, the eco-environmental vulnerability level of the Pearl River delta increased during the study period.